18O/17O abundance ratio towards a sample of massive star-forming regions with parallax distances. Issue 1 (5th April 2023) - Ou, Chao; Wang, Junzhi; Zheng, Siqi; Li, Juan; Romano, Donatella; Zhang, Zhi-Yu
ABSTRACT: The 18 O/ 17 O abundance ratio is, in principle, a powerful tool to estimate the relative contributions of massive stars and low- to intermediate-mass stars to the chemical enrichment of galaxies. We present 18 O/ 17 O ratios derived from simultaneous observations of C 18 O and C 17 O 1-0 towards 51 massive star-forming regions with the Institut de Radioastronomie Millimétrique (IRAM) 30 m telescope. Simultaneous observations of HC 18 O + 1-0 and HC 17 O + 1-0 with the Yebes 40m telescope towards five sources from this sample were also done to test the consistency of 18 O/ 17 O ratios derived from different isotopic pairs. From our improved measurements, resulting in smaller errors than previous work in the literature, we obtain a clear trend of increasing 18 O/ 17 O ratio with increasing Galactocentric distance (D GC ), which provides a significant constraint on Galactic chemical evolution (GCE) models. Current GCE models have to be improved in order to explain the observed C 18 O/C 17 O 1-0 gradient.